PENGALIHAN HAK KEPEMILIKAN HARTA PENINGGALAN OLEH AHLI WARIS SEBELUM DIBAGIKAN PERSPEKTIF HUKUM ISLAM DAN AKIBAT HUKUMNYA - Kawakib, Kawakib (Al-Usroh, 2024)
The aim of this research is to discuss inheritance law issues and the legal consequences of Mr "A" who sold his parents' inheritance secretly without the knowledge of his family and other heirs. Meanwhile, "M" (mayyit) still has debts owed to other people. This method is to use normative jurisprudence. The technique in this research uses data collection techniques in the form of interviews and documentation. The data analysis technique in this research uses descriptive-analytical analysis, then described, analyzed and concluded. Based on the research results, the main factor in transferring rights to inherited assets unilaterally before being distributed by Mr. The sales money was not distributed, amounting to 1.5 billion. Meanwhile, the simayyit (parents) still have outstanding debts that their parents have not paid during their lifetime worth 500 million to other people. According to Islamic law, "A" violated the law because he controlled other people's property and rights and neglected the forest of his deceased family member (parent). In positive law Article 1320 of the Civil Code). Article 834 Civil Code. Article 1365 of the Civil Code, including controlling and causing harm to other people and including embezzlement of inheritance, is regulated in Articles 372–376 of the Criminal Code. Article 376 of the Criminal Code. In Article 385 paragraphs (1) and (6), acts of land grabbing are punishable by a maximum prison sentence of 4 years in prison or a maximum fine of nine hundred rupiah.